2010
DOI: 10.1111/j.1365-294x.2010.04668.x
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting landscape epidemiology of two sympatric rabies virus strains

Abstract: Viral strain evolution and disease emergence are influenced by anthropogenic change to the environment. We investigated viral characteristics, host ecology, and landscape features in the rabies-striped skunk disease system of the central Great Plains to determine how these factors interact to influence disease emergence. We amplified portions of the N and G genes of rabies viral RNA from 269 samples extracted from striped skunk brains throughout the distribution of two different rabies strains for which stripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…We demonstrated that SCSK is genetically much more divergent than was inferred previously [3,14]. Evolutionary analysis did not show substantial evidence for positive selection in the dataset.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…We demonstrated that SCSK is genetically much more divergent than was inferred previously [3,14]. Evolutionary analysis did not show substantial evidence for positive selection in the dataset.…”
Section: Discussionsupporting
confidence: 43%
“…Studying patterns of sympatric circulation of SCSK and north-central skunk (NCSK) RABV in the territory of the Great Plains, Barton et al [14] suggested that SCSK may have an increased pathogenicity compared to the NCSK. However, such suggestions should be corroborated via appropriate biological experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in two studies in the USA on this species. No genetic structure was found among groups of skunks in a 61.6 km 2 study area in Texas [76], and a more recent study also failed to find significant genetic population structure over a larger area encompassing parts of North Dakota to Oklahoma (1,250 km 2 , [77]). Altogether, our results and previous evidence suggest a relatively high level of gene flow among groups of skunks which prevents population differentiation over a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most difficult parameters to estimate in pathogen dynamic models is transmission rate, because it depends on knowledge of contact structure among individuals in a population and the relationship between individuals and the virus [97, 39, 38]. Although mapping and other spatial tools have been helpful to understand rabies spread over landscapes, they have limited value in explaining intra-population dynamics and interactions among individuals [29, 98]. Also, conventional compartmental models (e.g., susceptible-infectious-recovered), often assume homogeneous contact structure, but this might not always apply to wildlife populations that have variable degrees of sociality, disease-induced behavioral changes, or other drivers of spatial mixing [99, 29, 39].…”
Section: Modeling Approaches To Understand Wildlife Rabiesmentioning
confidence: 99%